Hypoalbuminaemia and decreased midazolam clearance in terminally ill adult patients, an inflammatory effect? - Franken, Linda G. (Br J Clin Pharmacol, 2017)
AIMS: Midazolam is the drug of choice for palliative sedation and is titrated to achieve the desired level of sedation. Because of large inter‐individual variability (IIV), however, the time it takes to achieve adequate sedation varies widely. It would therefore greatly improve clinical care if an individualized dose could be determined beforehand. To find clinically relevant parameters for dose individualization, we performed a pharmacokinetic study on midazolam, 1OH‐midazolam (1‐OH‐M) and 1OH‐midazolam‐glucuronide (1‐OH‐MG) in terminally ill patients. METHODS: Using nonlinear mixed effects modelling (NONMEM 7.2), a population pharmacokinetic analysis was conducted with 192 samples from 45 terminally ill patients who received midazolam either orally or subcutaneously. The covariates analysed were patient characteristics, co‐medication and blood chemistry levels. RESULTS: The data were accurately described by a one compartment model for midazolam, 1‐OH‐M and 1‐OH‐MG. The population mean estimates for midazolam, 1‐OH‐M and 1‐OH‐MG clearance were 8.4 l h(−1) (RSE 9%, IIV 49%), 45.4 l h(−1) (RSE 12%, IIV 60.5%) and 5.1 l h(−1) (RSE 11%, IIV 49.9%), respectively. 1‐OH‐MG clearance was correlated with the estimated glomular filtration rate (eGFR) explaining 28.4% of the IIV in 1‐OH‐MG clearance. In addition, low albumin levels were associated with decreased midazolam clearance, explaining 18.2% of the IIV. CONCLUSION: Our study indicates albumin levels and eGFR as relevant clinical parameters to optimize midazolam dosing in terminally ill patients. The correlation between low albumin levels and decreased midazolam clearance is probably a result of inflammatory response as high CRP levels were correlated in a similar way.